2019
DOI: 10.1002/pits.22302
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between grit and academic achievement within K‐12 and higher education: A systematic review

Abstract: In recent years, grit has drawn increasing attention from both researchers and practitioners. As an important noncognitive indicator, grit has been used to understand individual success and performance in various fields. However, past empirical research has shown inconsistent findings on the relationship between grit and academic achievement. This study aims to review and synthesize past empirical findings on the relationship between grit and academic achievement. Forty‐four relevant articles involving a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
3
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 89 publications
(168 reference statements)
6
68
3
11
Order By: Relevance
“…Moreover, in line with the first hypothesis, the current findings supported that grit mediated the association between peer attachment and academic procrastination; to be specific, peer attachment was positively associated with grit, which in turn was negatively associated with academic procrastination. Such a finding is compatible with prior research indicating that peer attachment is positively associated with grit (Lan, 2019), and that grit is a positive facilitator of academic functioning (Wolters and Hussain, 2015; Lam and Zhou, 2019). The current study brings all these fractionated studies together, demonstrating the pathway from peer attachment to academic procrastination via grit.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, in line with the first hypothesis, the current findings supported that grit mediated the association between peer attachment and academic procrastination; to be specific, peer attachment was positively associated with grit, which in turn was negatively associated with academic procrastination. Such a finding is compatible with prior research indicating that peer attachment is positively associated with grit (Lan, 2019), and that grit is a positive facilitator of academic functioning (Wolters and Hussain, 2015; Lam and Zhou, 2019). The current study brings all these fractionated studies together, demonstrating the pathway from peer attachment to academic procrastination via grit.…”
Section: Discussionsupporting
confidence: 89%
“…Grit involves perseverance and passion for long-term goals, especially in the face of obstacles and adversities (Duckworth et al, 2007). To date, research has consistently shown the positive role of grit in facilitating academic functioning (Wolters and Hussain, 2015; Credé et al, 2017; Lam and Zhou, 2019), such as better academic performance and less tendencies to be academically procrastinated. For example, Wolters and Hussain (2015) found that grit is negatively related to academic procrastination in undergraduate students.…”
Section: Introductionmentioning
confidence: 99%
“…This integrative review has implications for advancing research programs about the generalizability, measurement, antecedents, and consequences of grit. First, although prior reviews (Credé et al, 2017 ; Datu et al, 2017a , b ; Credé, 2018 ; Lam and Zhou, 2019 ) primarily concentrated on summarizing the link of grit to academic performance and relevant outcomes, this review offers a more holistic overview about the correlates of grit through providing substantive summary on how grit and its dimensions predict optimal psychological, mental health, and physiological outcomes. Drawing from previous scientific findings about the consequences and correlates of grit, this review also organizes cognitive, affective, behavioral, and social mechanisms underscoring the educational, organizational, and mental health benefits of grit into the optimal performance and health (OPAH) model of grit.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Although existing reviews on grit (Credé et al, 2017 ; Datu et al, 2017b ; Credé, 2018 ; Lam and Zhou, 2019 ; Fernández et al, 2020 ) have provided comprehensive, detailed, and nuanced review on how grit tracks performance and other positive psychological outcomes, they have a number of considerable shortcomings. As these meta-analytic (Credé et al, 2017 ) and systematic (Datu et al, 2017b ; Lam and Zhou, 2019 ; Fernández et al, 2020 ) reviews primarily focused on summarizing the association between grit and domain-specific performance (e.g., achievement in school contexts), conclusions have myopic implications for understanding the role of grit in optimizing other equally important outcomes, such as psychological well-being and physical health. Moreover, previous reviews have paid little attention to summarizing studies on psychological processes underpinning the complex link of grit to a wide range of outcomes.…”
mentioning
confidence: 99%
“…Grit was reported to associate with a wide range of achievement indicators across different domains in earlier studies (Duckworth et al 2007;Eskreis-Winkler et al 2014); nevertheless, recent meta-analyses have indicated that grit is only weakly associated with achievement when evidence is aggregated (Credé et al 2017;Lam and Zhou 2019). The unique role of grit has also been questioned, as research has shown that grit-more specifically, grit's perseverance facet-is highly correlated with conscientiousness (Rimfeld et al 2016;Schmidt et al 2018).…”
Section: Grit and Achievementmentioning
confidence: 99%